Coordinated control and protection scheme for fault identification in hybrid three-terminal DC line based on pre-estimation of fault characteristics - Xincui Tian; Ziqian Liu; Jieshan Shan; Jinyun Yu; Jinxiong Wang; Qiang Li; Shihong Zhang; Tuoji Zhu; Jian Hu; Kaiwen Chen; Hongchun Shu (International Journal of Electrical Power & Energy Systems)
Under the traditional line protection approach, the problem of external faults not being addressed by the Peterson principle is resolved by solving the voltage and current fluctuation equations that satisfy the boundary conditions derived from the transmission line equations, this allows for the derivation of closed analytical solutions for the measured point voltages for different fault locations. In this paper, according to the threshold of the protection criterion, the pre-estimation of the fault point resistance and the fault pole selection are realized, a hybrid three-terminal DC line cooperative control and protection strategy based on estimated fault characteristics is proposed. Firstly, a start-up criterion considering estimated fault characteristics is constructed to achieve reliable start-up during high-resistance faults. Secondly, a ratio braking transverse differential protection is proposed to identify forward and reverse faults reliably. The control strategy is chosen based on the estimated fault characteristics, resulting in a comprehensive approach to cooperative control and protection of lines. The proposed method can quickly suppress the fault current by introducing a phase shift and negative input of converter voltage when a metallic fault occurs in the line. In the case of high resistance faults, the control system intentionally delays taking the action and waits for the control strategy to be corrected based on the results of the opposite end in the process. Multiple simulation scenarios show that the protection method is reliable and can quickly identify the line faults. The proposed method has effectively resolved the problem of high resistance in line protection through the process of “pre-estimation-correction”.